Revisiting Vietnam, 1st edition, 1st edition - Bleakney, Julia (Routledge, 2020)
This book explores the memorializing practices of American veterans of the Vietnam War at several of the most significant contemporary sites of memory in the United States and Vietnam. These sites include veterans' memoirs, museum exhibits, replicas of the National Vietnam Veterans Memorial, and tourism to Vietnam. Because war memorializing has, since the late 1960s, shifted focus from national soul searching to personal identity and recovery, I emphasize how contemporary narratives of the war, shaped more by memory than by history, often are detached from the specific history of the war and its political controversies. Drawing on trauma and cultural memory scholarship, as well as empirical data gathered during field research in the U.S. and Vietnam, the author examines how veterans' memorializing practices have become increasingly individualized, commodified, and conservative since the early 1980s.